Effect of Embryonic and Maternal Genotype on Embryo and Foetal Survival in Rabbit. Issue 3 (4th October 2012) - Vicente, JS; Llobat, MD; Jiménez‐Trigos, E; Lavara, R; Marco‐Jiménez, F
Contents: The aim of this work was to study the influence of embryonic and maternal genotype of two lines of rabbits selected by growth rate (line R) and litter size at weaning (line A) on prenatal survival. Embryos were recovered at 48 h of gestation from R and A donors (39 and 35 does, respectively) and reciprocally transferred to the oviducts of recipient does to the R (n = 15) and A (n = 14) lines. Each recipient doe received six embryos from line R into one oviduct and six embryos from line A into the other. Recipient does were examined by laparoscopy to determine implantation rate on day 14 and slaughtered on day 25 of gestation to determine the number of live foetuses and the weight of foetuses and placentas. No differences were found between lines in fertilization rate and stage of embryo development at 48 h post‐insemination. Implantation rate was affected by both the embryonic and maternal genotype. While embryos from donor line A had the highest implantation rate (0.78 ± 0.032 vs 0.65 ± 0.036 for line R), recipient line R had a better implantation rate (0.78 ± 0.033 vs 0.64 ± 0.036 for line A). Foetal survival was affected by the embryonic genotype. Embryos from donor line A had a higher foetal survival rate than embryos from donor line R (0.65 ± 0.036 vs 0.53 ± 0.038, respectively) but lower foetal and placenta weights. In conclusion, while embryonic genotype influenced both implantation and foetal survival rate, R embryos had the lowest rates, maternal genotype affected the implantation rate and R recipients may show a greater uterine receptivity during implantation period. Moreover, it must be observed that foetal and placenta weights were significantly affected by embryonic genotype and heavier for R line.